Building services and maintenance for air conditioner / Muhammad Firdaus A Hamid Faiz - A Hamid Faiz, Muhammad Firdaus (Universiti Teknologi MARA, Perak, 2022)
To complete this diploma course, we are required to undergo industrial training for 20 weeks as it is included in our course outline and need to be completed in our 5th semester of our diploma. This industrial training started from 23rd August 2021 until 7th January 2022 and during the industrial training we are monitored and supervised by the nominated supervisor. For my industrial training, this study at A&A MEGAH SDN. BHD. where it is located at Kuantan, Pahang. It is a contractor company doing building services maintenance and repair and other services. This company was established on 20th June 2020 by Encik Mohd Azlan Bin Mohd Jubli, the owner of this company. This company is expert in air conditioning installation, electrical work and building services such as housekeeping, painting, and laundering. The project that in this research is an installation and maintenance for the air conditioner at all Telekom Malaysia Berhad’s buildings. This study was assisted by my managing director who is the owner of the company to manage all the company organization such as office work and tender/quotation preparation including finishing all of the things that have been pending like example registration with the vendor and supplier. This research was also helped by my team doing this task as the company was a new fifth company from the founder. The conclusion is doing maintenance work for air conditioning to prevent any failure or system doesn’t working as required. My hope for this research will be useful for me as a reference in future.